Application of E-Learning As a Method In Educational Model to Increase The TOEFL Score In Higher Education - Abd Syakur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2019)
The study aims to determine the innovative learning influence based on Project Based Learning (PBL) towards the English learning outcomes of Brawijaya University Malang students. The research method using quasi-experimental design with the Times-Series Design with Control Group. The data analysis by using one way ANOVA test. The results showed that the TOEFL test treatment, namely the pre-test and post-test in the control class and the experimental class in the PBL model had differences. The average pre-test TOEFL score in the experimental class was 344.71 with score range from 300-397 and standard deviation of 29.386. The average post-test TOEFL score in the experimental class was 360.83 with score range from 303-400 and standard deviation of 24.146. Learning Based on PBL can improve student learning outcomes, the p-score at PBL was 0.026.